Fecal carriage and associated factors of extended-spectrum beta-lactamase-producing Enterobacteriaceae in children under five years old with diarrhea at a tertiary hospital in Tanzania - Emily M. Jackson; Doreen Kamori; Ambele M. Mwandigha; Vulstan J. Shedura; Upendo Kibwana; Mariam Mirambo; Agricola Joachim; Joel Manyahi; Mtebe V. Majigo (PLoS ONE, 2025)
Background The prevalence of extended-spectrum beta-lactamase-producing Enterobacteriales (ESBL-PE) is high in resource-limited settings. Carriage in young children has been linked to increased morbidity and mortality. However, there is limited information on the prevalence of ESBL-PE among children under five in our settings. This study aimed to determine the fecal carriage of ESBL-PE in children under five years old suffering from diarrhea at a tertiary hospital in Tanzania. Methodology This cross-sectional study was conducted over a three-month period at Muhimbili National Hospital in Dar es Salaam, Tanzania. Participants’ socio-demographic and clinical information were collected using a structured questionnaire and the child’s clinic card. Stool samples were collected and screened for the presence of ESBL-PE using MacConkey agar supplemented with ceftazidime. Confirmation of ESBL-PE was achieved through a double disk synergy test. Logistic regression analysis was employed to identify factors independently associated with ESBL-PE carriage. A p-value of less than 0.05 was considered statistically significant. Results We enrolled 181 children with a median age of 29 months (interquartile range: 20–37). The female-to-male ratio was 1:1. Among all participants, 54.1% (98/181) were malnourished, and the parents of 54.1% (98/181) had low levels of education. The overall fecal carriage rate of ESBL-PE was 65.7% (119/181). A total of 120 ESBL-PE isolates were confirmed. E. coli was the predominant ESBL-PE, contributing to (74.2%, 89/120), followed by K. pneumoniae (21/120, 17.5%), K. oxytoca (8/120, 6.7%), and Citrobacter spp. (2/120, 1.7%). Malnourished children had a higher carriage rate of ESBL-PE (77.6%) compared to non-malnourished children (51.8%) (p = 0.0003). Prolonged hospital stay (aOR=1.12, 95% CI = 1.05–1.19, p = 0.001), malnourishment (aOR=3.15, 95% CI = 1.61–6.19, p = 0.001), and a history of antibiotic use (aOR=2.28, 95% CI = 1.15–4.54, p = 0.018) were independently associated with the carriage of ESBL-PE. Furthermore, we observed that ESBL-producing E. coli isolated from malnourished children had high resistance rates of 75% and 65% against aztreonam and sulfamethoxazole/trimethoprim, respectively, while ESBL-producing K. pneumoniae isolated from the same group exhibited high resistance rates of 84.6% and 69.2%. Conclusion The present study revealed that children under five years old with diarrhea have a higher rate of ESBL-PE fecal carriage. Furthermore, prolonged hospital stays, malnutrition, and a history of antibiotic use are independently associated with ESBL-PE carriage. We also report high resistance rates of ESBL-PE isolated from malnourished children. These findings emphasize the importance of enhancing infection prevention and control measures to mitigate the spread of multidrug-resistant pathogens in both hospital and community settings.